2018
DOI: 10.3390/ijms19020468
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils: Beneficial and Harmful Cells in Septic Arthritis

Abstract: Septic arthritis is an inflammatory joint disease that is induced by pathogens such as Staphylococcus aureus. Infection of the joint triggers an acute inflammatory response directed by inflammatory mediators including microbial danger signals and cytokines and is accompanied by an influx of leukocytes. The recruitment of these inflammatory cells depends on gradients of chemoattractants including formylated peptides from the infectious agent or dying cells, host-derived leukotrienes, complement proteins and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 262 publications
(296 reference statements)
2
42
0
2
Order By: Relevance
“…Previous studies have demonstrated that exposure of the abraded corneal surface to LPS induces neutrophil recruitment to the corneal stroma in animal models 13 . Because LPS is well known to induce activation of the NLRP3 inflammasome, mice with LPS treatment of the cornea seem to be a useful model for investigating corneal inflammation induced by neutrophil infiltration and activation of NLRP3-mediated pro-inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that exposure of the abraded corneal surface to LPS induces neutrophil recruitment to the corneal stroma in animal models 13 . Because LPS is well known to induce activation of the NLRP3 inflammasome, mice with LPS treatment of the cornea seem to be a useful model for investigating corneal inflammation induced by neutrophil infiltration and activation of NLRP3-mediated pro-inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…4). Among these, IL-1β is the major inflammasome-related molecule, while the chemokine receptors (CCR1, CCR2, and CCR3) are involved in chemotaxis of white blood cells, including neutrophils 13,14 . Although the biological role, mechanism of expression, and cellular source of CCL8 under physiological or pathological conditions are poorly understood, recent reports have suggested that it may have potent pro-inflammatory activity 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Decreased corneal neutrophil recruitment and MPO activity are believed to be responsible for this phenomenon. 16 Kanagaratham et al 9 identified that fenretinide prevents recruitment of inflammatory cells to the airways after ovalbumin challenge. Similarly, Dong et al 17 demonstrated that fenretinide treatment blocked tumor angiogenesis with fewer M2-like macrophages in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…"Neutrophils are the most important first-line defence against bacteria, and are the first leucocytes to migrate to the site of infection. Activated macrophages are recruited to the joint slightly later, followed by T lymphocytes" [1]. To kill bacteria, neutrophils phagocytose the organisms secreting the content of their granules, producing reactive oxygen species and antimicrobial peptides, and releasing neutrophil * Simon Donell s.donell@uea.ac.uk 1 Norwich Medical School, University of East Anglia, Norwich, UK extracellular traps.…”
Section: Simon Donellmentioning
confidence: 99%